Improving Access to HIV/AIDS and Sexual and Reproductive Health Information and Services among Adolescents with Hearing Impairment in Ibadan, Nigeria: Protocol for a Pilot Cluster Randomized Controlled Trial - Adebayo, Emmanuel; Olumide, Adesola; Olaniyan, Halimat; Oluwagbayela, Babatunde (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context: Adolescents with hearing impairment are generally neglected in the design and implementation of most HIV information interventions. However, this group of adolescents significantly contributes to the rising incidence of HIV among adolescents. Aim: This study presents the protocol for a study that pilots an intervention to provide Sexual and Reproductive Health (SRH) and HIV information for adolescents with hearing impairment. Settings and Design: The study will be a cluster randomized control trial. The study will be conducted in two phases. Materials and Methods: Phase one will include information gathering about the current services available to adolescents generally and adolescents with hearing impairment across selected primary healthcare centers. The information obtained during this will be used to design the intervention. Phase two will be a pilot of the intervention to increase the comprehensive knowledge of HIV among adolescents with hearing impairment and link them to existing services. A pre-post intervention survey will be conducted to measure knowledge of SRH and HIV among the participants. Post-intervention surveys will occur immediately after and one-month post-intervention. Conclusion: This study will provide baseline information for a more robust study on improving access to information and services among adolescents with hearing impairment.